2015
DOI: 10.1186/s13601-015-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy in the Netherlands: differences in clinical severity, causative foods, sensitization and DBPCFC between community and outpatients

Abstract: BackgroundIt is unknown whether food allergy (FA) in an unselected population is comparable to those from an outpatient clinic population.ObjectiveTo discover if FA in a random sample from the Dutch community is comparable to that of outpatients.MethodsThis study was part of the Europrevall-project. A random sample of 6600 adults received a questionnaire. Those with symptoms to one of 24 defined priority foods were tested for sIgE. Participants with a positive case history and elevated sIgE were evaluated by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…The reported prevalence of food allergy is comparable to the in 1994 reported prevalence of s-rFA or food intolerance among 1483 Dutch adults, which was 12.4% [6] and the in 2015 reported prevalence of self-reported adverse reactions to Europrevall priority foods among 3 864 Dutch adults, which was 10.8% [8]. Although this would suggest that there has been no increase in the prevalence of food allergy over the last 24 years, we cannot exclude such an increase since our study population is larger and older compared to the study of 1994.…”
Section: Plos Onesupporting
confidence: 53%
See 1 more Smart Citation
“…The reported prevalence of food allergy is comparable to the in 1994 reported prevalence of s-rFA or food intolerance among 1483 Dutch adults, which was 12.4% [6] and the in 2015 reported prevalence of self-reported adverse reactions to Europrevall priority foods among 3 864 Dutch adults, which was 10.8% [8]. Although this would suggest that there has been no increase in the prevalence of food allergy over the last 24 years, we cannot exclude such an increase since our study population is larger and older compared to the study of 1994.…”
Section: Plos Onesupporting
confidence: 53%
“…Moreover, the foods listed are more likely to be involved in food intolerance based on a non-allergic adverse reaction and the DBPCFCs protocol was highly different from current standards [7]. In a more recent study, 25% of 3 864 Dutch adults reported adverse reactions to foods [8]. A meta-analysis described the prevalence of FA in European adults using the following definitions; s-rFA, s-rFA accompanied by positive sIgE and challenge proven FA [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we solicited 11011 adult females for self-reported allergy (SrFA) to any of 27 different foods and 21.5% reported sensitivity to one or more foods (Supplementary Table S1 ). That level is much higher than generally accepted estimates of 2–4% for the prevalence of food allergies (FA) based on the diagnostic gold standard of double-blind placebo controlled food challenge (DBPCFC), but not outside of the 10–30% estimates from previous studies that tabulated SrFA status 5 , 6 , 48 50 . Although one might presume that a large part of the difference between prevalence rates from SrFA and DBPCFC stems from patient subjectivity, some of the difference may be related to factors that augment allergic reactivity such as NSAID use, alcohol intake, exercise, menstruation cycle, and current pollen allergy season status 51 .…”
Section: Discussionmentioning
confidence: 71%
“…Risk communication is expected within the food industry, but it is not mandatory, so providing the industry with sensitive tests that can detect allergens at concentrations as low as reasonably achievable (ALARA) is the best way to ensure that unintentional allergen presence in food is monitored. In order for consumers to be entirely confident that their food is free from allergens, it is necessary to manufacture easy to use assays to detect unwanted allergen presence so that consumers do not have to rely on recall or notification data to maintain their avoidance diets [ 93 , 94 ]. A consumer-friendly allergen test that can be based on a smart-detector could provide consistent, essential information for the allergic individual, regardless of the quality of product labelling.…”
Section: Background On Food Allergensmentioning
confidence: 99%